2017
DOI: 10.1038/nn.4489
|View full text |Cite
|
Sign up to set email alerts
|

Pericyte degeneration leads to neurovascular uncoupling and limits oxygen supply to brain

Abstract: Pericytes are perivascular mural cells of brain capillaries that are positioned centrally within the neurovascular unit between endothelial cells, astrocytes and neurons. This unique position allows them to play a major role in regulating key neurovascular functions of the brain. The role of pericytes in the regulation of cerebral blood flow (CBF) and neurovascular coupling remains, however, debatable. Using loss-of-function pericyte-deficient mice, here we show that pericyte degeneration diminishes global and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
410
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 419 publications
(428 citation statements)
references
References 65 publications
(137 reference statements)
16
410
0
2
Order By: Relevance
“…Because previous studies in mice with deficient PDGFRβ signaling did not find the effect of gender on pericyte coverage, BBB integrity or blood flow regulation 17,22,30,32 both male and female mice at 2, 4-6, 12-16, and 36-48 weeks of age were used in the study. To determine the role for fibrinogen in F7/F7 mice we carried out pharmacological studies with ancrod and tranexamic acid (TXA) and genetic studies using fibrinogen-deficient and plasminogen-deficient mice, as described below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because previous studies in mice with deficient PDGFRβ signaling did not find the effect of gender on pericyte coverage, BBB integrity or blood flow regulation 17,22,30,32 both male and female mice at 2, 4-6, 12-16, and 36-48 weeks of age were used in the study. To determine the role for fibrinogen in F7/F7 mice we carried out pharmacological studies with ancrod and tranexamic acid (TXA) and genetic studies using fibrinogen-deficient and plasminogen-deficient mice, as described below.…”
Section: Methodsmentioning
confidence: 99%
“…Pericytes control microvascular functions in neuron-dense grey matter regions including blood-brain barrier (BBB) permeability 1517 and cerebral blood flow 1822 . They die in AD 10,2326 mild dementia 27 , stroke 19,20 and cerebral autosomal dominant arteriopathy with subcortical infarcts (CADASIL), the most common genetic ischemic small vessel disease associated with cognitive impairment 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Pericyte-endothelial contact is critical for many vascular homeostatic functions, and it remains to be seen how modulation of pericyte structural plasticity on a broad level affects cerebral blood flow regulation, metabolite exchange, BBB integrity, and microvascular architecture. Whether capillary pericytes are involved in cerebral blood flow regulation is controversial (Attwell et al, 2015; Hill et al, 2015; Kisler et al, 2017). Our data suggests that pericyte loss leads to capillary dilation under basal conditions, which may decrease capillary flow resistance and alter metabolic exchange.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study in pericyte-deficient mice reported a reduction in functional hyperemia, a lowering of brain O 2 levels, and a loss of neurons in older animals (Kisler and others 2017). Although a reduction in capillary density was observed in these animals, which could have effects on the brain not directly related to the functional hyperemia response, the results indicate that functional hyperemia is important in maintaining neuronal health.…”
Section: The Function Of Functional Hyperemiamentioning
confidence: 99%
“…Existing computational analyses must be complemented by physiological experiments assessing the effect of capillary dilation on blood flow. Targeting capillary pericytes will be useful in answering this question (Kisler and others 2017). …”
Section: Remaining Challengesmentioning
confidence: 99%